Effects of Pneumatic Defoliation on Fruit Quality and Skin Coloration in ‘Fuji’ Apples - Nay Myo Win; Jingi Yoo; Van Giap Do; Sangjin Yang; Soon-Il Kwon; Hun-Joong Kweon; Seonae Kim; Youngsuk Lee; In-Kyu Kang; Juhyeon Park (Agriculture)
Fruit skin color and physical quality are important for customer acceptability and market value. Therefore, this study aimed to evaluate the effect of pneumatic defoliation on the fruit quality, coloration, and anthocyanin content of ‘Fuji’ apples. Apple trees were subjected to no defoliation (control) and defoliation at low (0.6 bar) and high (0.9 bar) air pressure 20 days before harvest at 1 km/h of tractor speed. High-defoliation treatment increased the leaf damage rate but did not significantly affect the defoliation rate compared to low-defoliation treatment. Additionally, photosynthetically active radiation and solar irradiance inside the tree canopies were highest in the high-defoliation group, followed by the low-defoliation and control groups. With the exception of higher firmness in the high-defoliation treatment, pneumatic defoliation treatments had little effect on fruit size and weight, titratable acidity, soluble solids content, the starch pattern index, and the sunburn incidence of fruit. Compared with that of the control group, both defoliation treatments significantly increased the a* and C values and decreased the ho values of the fruit color. Moreover, both defoliation treatments significantly increased anthocyanin content and upregulated the anthocyanin biosynthesis genes (MdPAL, MdCHS, MdCHI, MdF3H, MdANS, MdANS, MdUFGT) and the transcription factor (MdMYB10). A Pearson′s correlation analysis also showed that anthocyanin production was strongly correlated with each of the anthocyanin biosynthesis genes, especially in the pneumatic defoliation treatments. Conclusively, the results show that pneumatic defoliation at low pressure bars could be an effective strategy for improving the red coloration of ‘Fuji’ apples.